PERSEPSI WISATAWAN TERHADAP KUALITAS PELAYANAN PRAMUWISATA DI BALI - Ida Bagus Saskara Putra; I Made Kusuma Negara; Ni Made Sofia Wijaya (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2017)
Tour guide has an importan role in tourism activities. It can be seen from the function of a tour guide as such are conduits for privileged 'inside' information on the tourist destination. The purpose of this study is to find out how the tourist perception to the quality service of tour guide in Bali.Data collection techniques used in this research is a questionnaire and literature study for determine this sample was using purposive sampling by gave questionnaires to 400 respondents. The data was analysis used descriptive quantitative. There are two types of respondents, domestic tourists numbered 263 respondents and foreign tourists numbered 137 respondents, each divided according to the proportional 0.05. This study used five variables and consists of twenty indicators.Data collection techniques used in this research is questionnaires and literature study. In determining the sample was using purposive sampling by distributed questionnaires to 400 respondents. Data analysis techniques used in descriptive quantitative. There are two types of respondents domestic tourists amounted to 263 respondents and foreign tourists numbered 137 respondents, each divided according to the proportional 0.05. This study uses five variables and consists of twenty indicators.The results of this research is the tourist perception overall consisting of domestic and foreign tourists can be concluded, tourists perception of the tour guides service quality in Bali is already very good.